Analysis of Employee Competence, Service Quality, and Credit Procedures on Customer Satisfaction Through Customer Decisions to Choose Kredit Jatim Micro at Bank Jatim Malang Branch - Lina Damayanti (Sean Institute, 2025)
This study aims to analyze the effect of employee competence, service quality, credit procedures, and customer decisions to choose credit products on customer satisfaction at Bank Jatim Malang Branch. The research employed a quantitative approach using multiple linear regression analysis. Data were collected through a survey using questionnaires distributed to 100 customers who had used the Kredit Jatim Micro product. Data analysis was conducted using F-tests to examine the simultaneous influence of the independent variables on the dependent variable, and t-tests to evaluate the partial effects of each variable. The results showed that employee competence, service quality, credit procedures, and customer decisions to choose credit simultaneously had a significant effect on customer satisfaction, with an F-value of 13.45 and a significance level of 0.000. Partially, employee competence and service quality had a more dominant influence on customer satisfaction compared to credit procedures and customer decision-making. Based on these findings, it is recommended that Bank Jatim Malang Branch continues to improve employee competence and service quality, as well as simplify credit procedures to enhance customer satisfaction and loyalty.